A Long Obedience in the Same Direction : Discipleship in an Instant Society - Peterson, Eugene H., 1932-2018. (Downers Grove, Ill. : InterVarsity Press, 1980)
This world is no friend to grace. God has given us some resources, however. As we grow in character qualities like hope, patience, repentance and joy, we ill grow in our ability to persevere. The biblical passages in these studies offer encouragement to continue in the path Christ has set forth for us. There is a clean, bright rigor to honest life before God. Burnishing the language of the Psalms, Eugene Peterson makes that life sing like a taut wire. A Long Obedience is the only path of discipleship to Jesus, and this is a message we desperately need to hear and implement today.
1. Discipleship: ""What Makes You Think You Can Race Against Horses?"" 2. Repentance: ""I'm Doomed to Live in Meshech"" 3. Providence: ""God Guards You from Every Evil"" 4. Worship: ""Let's Go to the House of God!"" 5. Service: ""Like Servants ... We're Watching & Waiting"" 6. Help: ""Oh, Blessed Be God! He Didn't Go Off & Leave Us!"" 7. Security: ""God Encircles His People"" 8. Joy: ""We Laughed, We Sang"" 9. Work: ""If God Doesn't Build the House"" 10. Happiness: ""Enjoy the Blessing! Revel in the Goodness!
Includes bibliographical references.
Keywords: Bible. -- Meditations; Perseverance -- Biblical teaching; Meditations; Meditations